BUILDING CAPACITY AND ENHANCING KNOWLEDGE OF THE HEALTHCARE PROVIDERS REGARDING HEALTHCARE FINANCING IN PAKISTAN - Naeem, Nawal; Aslam, Rida; Kumar, Naveen; Raza, Iram; Naeem, Kashaf; Kumar, Ramesh (Journal of Ayub Medical College Abbottabad, 2024)
Background: The Office of Research, Innovation, And Commercialization (ORIC) of the Health Services Academy in Collaboration with the Punjab Employees Social Security Institution (PESSI) and the German Corporation for International Cooperation (GIZ) organized and conducted a 2-day training workshop on “Healthcare Financing”. This was intended to learn about healthcare finance by analyzing government regulations, private companies, and international collaboration. Explore various funding sources for healthcare, observe how healthcare operates around the world, and devise effective money management strategies so that healthcare can expand and benefit everyone. This paper reports on the training program, which aims to train healthcare providers on the concepts of healthcare financing and build their understanding and knowledge of healthcare systems, models, and implementation of intelligent financing strategies for sustainable financial growth and organizational success. Methods: A team of experts developed the curriculum and its accompanying material. Initial training was given to the healthcare providers of all participating institutions. Staff from public and private hospitals enrolled in the training and other frontline healthcare workers were invited. Four types of educational material were produced and used; a guidance booklet, a training video, and a set of PowerPoint presentations to explain the HCF and its importance. Results: A 2-day training workshop was conducted in which the pre- and post-knowledge regarding the HCF of all the participants was assessed. All the participants belonged to public health fields and all of the participants were public health experts. Conclusion: With limited resources and in a short period, the ORIC with the collaboration of PESSI and GIZ trained a good amount of healthcare workers to address the complex challenges and opportunities within the industry and key aspects of healthcare financing, from the evolving payment mechanisms and emerging trends to the global perspective on funding health initiatives